Public Policy Analysis of the Development of Pantai Indah Kapuk 2 (PIK 2) - Arif Nugroho; Eva Latifah; Pryo Handoko; Yudi Yudistira (Neo Journal of economy and social humanities, 2024)
This research analyzes the public policy of the Pantai Indah Kapuk 2 (PIK 2) development, a project covering 1,755 hectares in northern Jakarta, aimed at enhancing economic growth and providing facilities for the community. Despite its significant potential, the project faces substantial challenges, including social impacts such as the displacement of local communities and threats to the mangrove ecosystem. Through a qualitative approach, the research finds that the implementation of PIK 2 often neglects community participation and environmental impacts. Recommendations include the need for an inclusive approach in policy formulation and ongoing evaluation to ensure sustainable benefits for all stakeholders.